Predictors of Survival in Esophageal Squamous Cell Carcinoma with Pathologic Major Response after Neoadjuvant Chemoradiation Therapy and Surgery: The Impact of Chemotherapy Protocols. (4th October 2016) - Li, Chia-Ying; Huang, Pei-Ming; Chu, Pei-Yi; Chen, Po-Ming; Lin, Mong-Wei; Kuo, Shuenn-Wen; Lee, Jang-Ming
Abstract : Tumor recurrence is an important problem threatening esophageal cancer patients after surgery, even when they achieve a pathologic major response (pMR) after neoadjuvant concurrent chemoradiation therapy (CCRT). The predictors related to overall survival and disease progression for these patients remain elusive. We aimed to identify factors that predict disease progression and overall survival in esophageal squamous cell carcinoma (SCC) patients who achieve a pMR after neoadjuvant CCRT followed by surgery. We conducted a retrospective study to analyze the factors influencing survival and disease progression after esophagectomy for esophageal cancer patients who had a major response to CCRT, which is defined by complete pathological response or microscopic residual disease without lymph node metastasis. From our study cohort, 285 patients underwent CCRT and subsequent esophagectomy; 171 (60%) of these patients achieved pMR. After excluding patients with lymph node metastases, incomplete clinical data, and adenocarcinomas, we enrolled 117 patients in this study. We found that the CCRT regimen was the only factor that influenced overall survival. The overall survival of the patients receiving taxane-incorporated CCRT was superior to that of patients receiving traditional cisplatin and 5-fluorouracil (PF) (P = 0.01 1 ). The CCRT regimen can significantly influence the clinical outcome of esophageal SCC patients who achieve pMR after neoadjuvant CCRT and esophagectomy. Incorporation of taxanes into cisplatin-based CCRT may be associated with prolonged survival.